2006
DOI: 10.1111/j.1439-0507.2006.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral nystatin prophylaxis to prevent invasive candidiasis in Neonatal Intensive Care Unit

Abstract: The use of oral nystatin to prevent fungal colonisation and infection in neonates in the Neonatal Intensive Care Unit (NICU) is still an open question and not yet recommended as a standard of care. To determine whether prophylactic oral nystatin results in a decreased incidence of invasive candidiasis in the newborn infants, a total of 3991 infants were divided randomly into two groups. Group A infants (n = 1995), only those neonates who were identified as yeast carriers (oral moniliasis) were treated with ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
58
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 37 publications
10
58
1
Order By: Relevance
“…Prophylaxis started after the infant is colonized may not be as effective as starting prophylaxis shortly after birth. Infants weighing over 1000 g with gastrointestinal disease also have a high rate of developing ICI and a RCT in this population is also needed [40].…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylaxis started after the infant is colonized may not be as effective as starting prophylaxis shortly after birth. Infants weighing over 1000 g with gastrointestinal disease also have a high rate of developing ICI and a RCT in this population is also needed [40].…”
Section: Future Researchmentioning
confidence: 99%
“…A recent prospective single-center study examined nystatin prophylaxis (100,000 units three-times daily orally or via a nasogastric tube) in both preterm and term NICU patients, excluding infants with congenital defects requiring surgery [40]. Examining the study infants by birth weight, 24% (n = 948) weighed under 1500 g, 8.7% (n = 349) weighed under 1000 g and 0.8% (n = 30) weighed under 750 g. Infants were randomized into two groups: group A had oral fungal cultures performed and received nystatin prophylaxis only if oral Candida colonization was isolated and group B infants were given prophylaxis regardless of colonization status.…”
Section: Nystatinmentioning
confidence: 99%
“…Interestingly, there was a considerable amount of variation in the definitions used for both colonization and systemic infection, as well as in the observed colonization rates among these studies (Sims et al [5] 44%, Ozturk et al [6] 24.7%, Ganesan et al [7] 35.5%, Wainer et al [9] 35.2% [Howell et al (8) did not study colonization rates]). These studies were also conducted at different times periods and in different countries (United States, Turkey, United Kingdom, Australia and South Africa).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Cochrane review on this topic (10), which included three of the articles described here (5,6,9), concluded that the data were insufficient to guide clinical practice. The present systematic review used the two databases searched in the Cochrane review (MEDLINE and EMBASE) but further extended the search to include Scopus, Web of Science and CINAHL.…”
Section: Discussionmentioning
confidence: 99%
“…We are following the dosing system written in the Neofax, a neonatal dosage booklet by Young and Mangum. Our standard of Candida treatment is to start with intravenous fluconazole prophylaxis from day 7 of life, use oral mycostatin in colonized babies, and start with amphotericin B with any proved or highly suspected infection [9,10]. However, for the resistant infection, we do not have a fixed protocol, we go by the discretion of the consultant neonatologist on service and with the help of the microbiologist.…”
Section: Discussionmentioning
confidence: 99%